Performance Degradation Evaluation of Rolling Bearing based on Improved Fuzzy Entropy and Grey Relation - Li Cheng; Wensuo Ma; Xintao Xia; Liangwen Wang (Jixie chuandong)
In light of low sensitivity of fuzzy entropy in extracting degraded features of rolling bearing，an improved fuzzy entropy based on the sigmoid-like function is proposed. Aiming at the localization issues of assessment methods for traditional rolling bearing performance degradation，a novel performance degradation evaluation method based on grey relation is proposed. This method uses grey relation theory to evaluate the relationship between extracted rolling bearing degradation characteristics and reliability，so as to achieve the purpose of evaluating the degradation features of rolling bearing from the overall perspective of rolling bearing reliability evolution. The experimental results show that the improved fuzzy entropy can accurately extract the performance degradation features of rolling bearing，and the rolling bearing degradation features extracted based on the improved fuzzy entropy have a consistent evolution law with the rolling bearing maintaining reliability，with a credibility level above 95%.